Propriedades dos microconcretos fabricados com agregados contaminados por resíduos de gesso - Alexandre Lopes Vieira (2008)
The use of plaster in the construction has enlarged a lot in the last few years; mainly as internal coating of walls replacing the conventional process (mortar). However this type of activity is a big generator of residues due to the time of application and the techniques used in the process. Because these residues arent segregated, they are stored in the construction place all together with the residues from other materials and its discard is done in sanitary embankments. These residues are denominated RCDs (residues of constructions and demolitions) and when they are not contaminated by plaster residues, they could have had a different destiny; they could be reused in the production of aggregate, substituting the natural ones in the concrete production. The RCDs when they are sent to the plant in order to product aggregate can have plaster pollution because the control is done only by visual manner. An aggregate of RCD without plaster could have, even though, a tiny and imperceptible quantity of plaster and such aggregates when they are used in the production of concrete, they provoke can cause expansible reactions, decreasing thus its useful life. So, having all these facts in account, the study of concrete made with different rates of plaster residues becomes very important and interesting. In this paper the influence of this pollutant is analyzed in the concrete properties manufactured without great aggregate (microconcrete). The tests results for resistance to compression at the age of 150 days show a damage of strength when compared to the results of 28 days, due to the etringita formation in microconcretes with contaminants.